JUDICIALIZAÇÃO DA EDUCAÇÃO INFANTIL EM TEMPO INTEGRAL: UM ESTUDO DE CASO DO MUNICÍPIO DE VITÓRIAES - Auer, Franceila (2021)
This study aims to question the phenomenon of ongoing judicialization with the demand for vacancies in full-time early childhood education. It adopts the case study as a methodology, using the document analysis of extralegal and legal lawsuits as a research tool. It uses the software NVivo to assist and organize data analysis. Eight lawsuits filed by families demanding vacancies with the Public Ministry and Court of Justice for their children in public institutions of full-time early childhood education in the municipality of Vitória, located in the state of Espírito Santo, were analyzed. The results show that most of the families point to the non-home-based work and the socioeconomic needs as the main reasons to meet the demands for vacancies in full-time early childhood education. However, the demands are not always accepted in favor of the vacancies, since there is a tension in the field of early childhood education due to fact that the full-time education is not compulsory, especially in the kindergarten and the priority assumed with part-time pre-school. The workers of Legal System substantiate the lawsuits using repeatedly legal and also constitutional arguments, moreover, they point to categorical imperatives, although few of them, inspired by the understanding of right to education as a responsibility of public policies. In the light of Hannah Arendt’s thought, it assumes the conception of right as a public phenomenon that pertains to everyone and not only to an abstract right put in legal norms. It is concluded that the judicialization has been conducting the right in a discriminated way – since it is a possibily of access to education only for some children, whose families are aware of the legal norms, while other children continue to be excluded – which may be ocurring within society due to a lack of recognition of right as an experience arising from the political action.